Factors Associated with Stunting in Children Aged 6-24 Months in Noelbaki Village - Berthinus Vichtorus Dhenga Teti; Afrona E. L. Takaeb; Dominirsep O. Dodo; Engelina Nabuasa (Universitas Nusa Cendana, 2023)
Stunting is an impaired physical and cognitive growth posed by a chronically inadequate intake and repeated chronic infections. In 2018, 1,298 cases ranked Tarus Health Center as the health center with the most stunting cases in Kupang Regency. In 2019, it fell to 416 points and rose to 538 topics in 2020. Noelbaki Village contributes to the high stunting incidence, with 49 cases in children aged 6-24 months. This study aimed to determine the factors associated with stunting in children aged 6-24 months in Noelbaki Village. This study is an analytical study with a case-control design performed in 98 samples with a ratio of 1:1, with 49 children as the case group and 49 as the control group. The sampling technique used was total sampling, using chi-square test analysis. The results show that nutritional intake (OR=9,750, 95%CI 3,483-24,737; p=0,000) was the most factor attributed to the incidence of stunting, followed by complementary feeding (OR=8,538 95%CI 3,441-21,190; p=0,000) exclusive breastfeeding (OR=7,654 95%CI 3,028-19,351; p=0,000) and infectious diseases (OR=6.923 95%CI 2.852-16.804; p=0,000) while immunization status and basic sanitation were not contributing factors to stunting incidence. Health agencies are expected to be able to engage with the community in efforts to improve nutritional quality by focusing on the movement of exclusive breastfeeding and complementary feeding and the prevention of infectious diseases in children.